Effectivity Of Agroedutourism To Strengthen Healthy Agro-Ecosystem Awareness Of Students In Some Elementary Schools In Malang Raya, East Java - Hanin Niswatul Fauziah; Endang Arisoesilaningsih; Bagyo Yanuwiadi (Journal of Indonesian Tourism and Development Studies, 2013)
This research aimed to study the effectivity of agroedutourism to strengthen students’ environmental awareness, especially concerning on importance of rice organic farming system. Eighty three students were invited joining the program. They were the 5th grade of three elementary schools (SDN Ketawanggede 2, SDI Surya Buana and SDN Sumberngepoh 02). It was provided three agroedutourism programs, i.e. two outdoors programs (Farmers’ friends and enemies, Plants for biopesticide and natural attractant), as well as the indoor session called Healthy agroecosystem. Including the programs were joining ecoeco-games and tasting some food (steamed rice-bran brownies, organic red rice milk and zalacca fruits). Effectivity of the programs was evaluated using questionnaire. Data were analyzed by SPSS program using Wilcoxon test (α=0,05). Results showed overall that the agroedutourism increased significantly students cognitive, affective and even their appreciation to agricultural environment. Students of SDN Sumberngepoh 02 showed a highest agro-environmental awareness. While, the highest cognitive improvement was gained by students of SDI Surya Buana (76%), followed by SDN Ketawanggede 2 (62%) and SDN Sumberngepoh 02 (47%). The most interesting program was an outdoor namely Farmers’ friends and enemies, while they preferred a steamed rice-bran brownies than the other one. They were exciting joining some eco-games especially predator and prey as well as guest animal name and its role. It seemed that the outdoor programs were more appreciated rather than the indoor one. Keywords: Agroedutourism, awareness, effectivity, healthy agro-ecosystem